2012
DOI: 10.1136/bmjspcare-2012-000224
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of the impact of massage therapy on sources and levels of distress in brain tumour patients

Abstract: This study further documents that brain tumour patients report high levels of distress across the disease course. However, participants in this study reported improvements in distress level and total number of sources of distress while receiving massage therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Our findings bolster previous research which suggests massage is helpful for cancer patients' anxiety and distress [18][19][20][21][22][23]. It also extends the body of knowledge of studies that compare pre-to post-massage anxiety scores [19,20,22,23].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings bolster previous research which suggests massage is helpful for cancer patients' anxiety and distress [18][19][20][21][22][23]. It also extends the body of knowledge of studies that compare pre-to post-massage anxiety scores [19,20,22,23].…”
Section: Discussionsupporting
confidence: 81%
“…Patient-reported distress and emotional discomfort measures have also significantly improved after OM [21,22]. Additionally, those who receive OM have significant and lasting improvements in quality of life measures following therapy [21,23,24].…”
Section: Introductionmentioning
confidence: 97%
“…Massage is one of the oldest forms of healthcare and has been reported to have beneficial effects on various physical and psychological conditions (Field, 2016 ; Moraska, Pollini, Boulanger, Brooks, & Teitlebaum, 2010 ), commonly used for cancer, palliative care and pain management (Alves, Gonçalves Jardim, & Pereira Gomes, 2017 ; Boitor, Gélinas, Richard-Lalonde, & Thombs, 2017 ; Crawford et al, 2016 ). Reported mental benefits of massage include improvements in distress level (Keir & Saling, 2012 ), decreased depression (Alves et al, 2017 ; Field, 2014 ), stress reduction (Turkeltaub, Yearwood, & Friedmann, 2014 ), anxiety reduction (Alves et al, 2017 ;Brand, Munroe, & Gavin, 2013 ), and the promotion of wellbeing (Alves et al, 2017 ; McFeeters, Pront, Cuthbertson, & King, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that TM reduced physiological stress, pain and psychological distress and improved mood [14,17]. The positive effects of TM start immediately and are maintained for 48 hours following treatment [18].…”
Section: Short Communicationmentioning
confidence: 95%